Leptospira spp. Prevalence in Small Mammal Populations in Cotonou, Benin. (27th March 2013) - Houemenou, G.; Ahmed, A.; Libois, R.; Hartskeerl, R. A.
Abstract : The aim of this study was to assess the Leptospira prevalence in small animals in Cotonou, the capital of Benin. Rodents and shrews were captured in urban and periurban settings and determined as species of the genera Rattus, Mastomys, and Crocidura . Kidney specimens of 90 animals were examined using a real-time PCR assay specific for leptospires that belong to pathogenic species. Leptospiral DNA was amplified from kidney tissues ranging from 13.3% (8/60) in Rattus rattus to 100.0% (1/1) in Crocidura spp. with an average of 18.9% (17/90) of the animals caught at 15 locations. Clade-specific Taqman PCR on 10 samples placed six of these within clade 1 comprising the species L. kirschneri, L. interrogans, L. meyeri, and L. noguchii and four within clade 2 consisting of species L. weilii, L. alexanderi, L. borgpetersenii, and L. santarosai . Phylogenetic analysis of partial sequences of the amplicons of seven samples of these 10 samples revealed that four of the clade 1 samples could equally be assigned to L. interrogans and L. kirschneri and three samples from clade 2 belonged to L. borgpetersenii . Results presented in the paper indicate that small mammals present a major public health risk for acquiring leptospirosis in Cotonou, Benin and will contribute to a raised awareness amongst health care workers and decision makers and hence promote appropriate clinical management of cases.